Implementation of the Customer Relationship Management Scorecard and AHP Methods in the Manufacturing Industry: Implementasi Metode Customer Relationship Management Scorecard dan AHP Pada Industri Manufaktur - Mauludhin, Ahmad Yudha; Jakaria, Ribangun Bamban (Universitas Muhammadiyah Sidoarjo, 2023)
PT X is a company in the manufacturing sector of the paint industry Competition in the paint industry fighting for market share. To form relationships with customers used customer relationship management method. This study aims to determine the results of implementing the CRM Scorecard. Researchers collect search data from literature or interviews with experts in the field of customers. From the search results, the data yields perspectives and Key Performance Indicators for each perspective, namely customer knowledge, interaction,value and satisfaction. From the perspective and indicators of the CRM Scorecard, it will be determined by weighting using the Analytical Hierarchy Process method. Significant results for company evaluation were obtained from CRM assessments using the AHP method, namely value (0.3737) and Satisfaction (0.34) obtaining the highest ratings indicating that the company is in line with the objectives of these two perspectives, namely creating corporate value and create customer loyalty to the company.